(untitled) (Bangladesh Journal of Neurosurgery, 2022)
Background: Arachnoid cysts are fluid-filled sacs that occur on the arachnoid membrane that covers the brain. In most of the cases these cysts are asymptomatic and do not require any treatment. Only symptomatic arachnoid cysts require treatment. Objectives: The objective of this study was to see the results of microsurgical treatment of intracranial arachnoid cyst. Methods: This retrospective cross sectional study was carried out in the Department of Neurosurgery, National Institute of Neurosciences & Hospital, Dhaka, Bangladesh. Total 15 cases were included in this study for a period of 3 years. Data were collected including their operation procedures and follow up by questionnaires and finally observed the results. Results: Among the 15 patients about one third were presented in the second decades of life with male predominant. Significant clinical improvement was observed among most of the patients. The radiological decrease of the size of the cysts was also found. The results of microsurgical excision were better than other procedures. Conclusions:Surgical treatments are needed only in symptomatic cases. Clinical and radiological outcome of the surgical treatment is satisfactory. Bang. J Neurosurgery 2021; 11(1): 13-17